(untitled) (Journal of the Medical College for Women & Hospital, 2026)
Background: Breast abscesses, are a very common clinical entity identified in daily practice. At an initial presentation it may be treated conservatively with antibiotics. Minimal invasive surgery is replacing the traditional management. Aim: To compare the outcome and effectiveness of ultrasound guided percutaneous needle aspiration with conventional incision and drainage in management of small breast abscess. Methodes: This Quasi-experimental study was conducted in the Department of Surgery, Sir Salimullah Medical College Mitford Hospital, Dhaka from July 2023 to June 2024. A total 50 female patients with the diagnosis of breast abscess were included according to selection criteria and then divided into 2 groups by alternative consecutive manner (Group-A and Group-B). After proper evaluation, informed written consent was obtained. In group A, patients were treated by ultrasound guided percutaneous aspiration with 19G needle under local anesthesia. In group-B, patients were treated by conventional incision and drainage under general anesthesia. Data was sorted and analyzed by SPSS 26 version. Independent sample t test and Chi-Square test were performed as applicable. Results: In this study, mean duration of procedure was 15.64±3.33 min in group A and 31.48±7.05 min in group B. VAS score was 2.72 ± 1.28 in group A and 5.28 ± 1.28 in group B. The time required for the procedure and VAS score in Group A were significantly (p<0.001) less than Group B. In group A, 9 (36%) patients showed resolution of the abscess on a single aspiration, while 10 (40%) patients required two aspirations, 2 (8%) patients needed three aspirations for resolution and 4 (16%) patients were not resolved even after three aspirations and hence were treated by Incision and Drainage and their follow up schedule was like group B. We observed that all lactating women continued their breastfeeding from the day of aspiration (0.00±0.00 POD) in group A than women who underwent incision and drainage in group B (12.33±2.32). In this study, mean number of hospital visit was 4.88±2.35 times in group A and 12.96±3.88 times in group B and duration of complete resolution was 14.48±3.73 days in group A and 24.60±3.92 days in group B. This difference was statistically significant (p<0.001). We observed that all patients had satisfactory cosmesis after aspiration and all the patients developed scar mark after incision and drainage. Conclusion: It can be concluded that ultrasound guided percutaneous needle aspiration is a simple, safe, effective and could be a widely accepted procedure for management of small breast abscess. J Med Coll Women Hosp.2026; 22(1): 108-115